Toward an all-IP-based UMTS system architecture. - Bos, L.
Looking into the future, two main drivers for the mobile telecommunications market can be identified: third-generation mobile systems (e.g., UMTS) and the Internet (e.g., the introduction of IP technologies like voice/multimedia over IP in mobile networks). UMTS is seen as the enabler of wireless multimedia applications and portability of a personalized service set across network/terminal boundaries, as defined within the virtual home environment (VHE) system concept. In light of these evolutions, this article investigates the impact of the evolution toward an all-IP UMTS network architecture on the UMTS service architecture, which is based on the VHE concept. The article discusses two possible scenarios for supporting VoIP services in the UMTS service architecture and analyzes their applicability in an all-IP-based UMTS network. The first is based on the traditional centralized IN service architecture. The second proposes a new decentralized architecture based on direct control of VoIP call control equipment by open service architecture interfaces
Keywords: Internet; VoIP call control equipment; VoIP services; All-IP UMTS network architecture; All-IP-based UMTS system architecture; Centralized IN service architecture; Decentralized architecture; Mobile networks; Mobile telecommunications market; Multimedia over IP; Open service architecture interfaces; Personalized service set portability; Third-generation mobile systems; Virtual home environment system; Voice over IP; Wireless multimedia application